Mechanical Behavior of Cracked Rock in Cold Region Subjected to Step Cyclic Loading - Liang Zhang; Fujun Niu; Minghao Liu; Jing Luo; Xin Ju (Geofluids)
In order to analyze the mechanical behavior of cracked rock in cold region subjected to cyclic loading, step cyclic loading and unloading (SCLU) triaxial tests with different stress paths have been designed. The mechanical responses such as strength, deformation, and failure mode were analyzed. The test results show that limestone has obvious strengthening effect under cyclic loading due to local crushing and filling of internal structural plane. The strengthening effect and fatigue damage effect caused by cyclic loading and the impact damage effect caused by the upgraded of stress level have an effect on mechanical response of cracked rock, and the degree of influence is related to the stress path. Under the stress path of constant stress lower limit (CSLL), the strengthening effect of rock was more prominent and its strength was enhanced. It was mainly subjected to progressive fatigue damage and had a buffering effect in the failure process. However, under the stress path of increasing the stress lower limit (ISLL), the rock suffered significant impact damage and entered the fatigue damage stage in advance, which led to its strength reduction and sudden failure when entering the next stress level. In addition, during the loading process, larger initial stress amplitudes led to more obvious cyclic strengthening effects, while smaller initial stress amplitudes led to greater plastic deformation and energy dissipation, and the rock was more prone to progressive damage.